O komputerowym modelowaniu niezawodności stalowych wież telekomunikacyjnych - Kamiński, Marcin; Szafran, Jacek (Wydawnictwo Politechniki Łódzkiej, 2010)
Tematem niniejszej pracy jest zastosowanie analizy numerycznej opartej na uogólnionej metodzie perturbacji stochastycznej i funkcji odpowiedzi do wyznaczenia wskaźników niezawodności dla stalowych wież telekomunikacyjnych. Wskaźniki te wyznaczono za pomocą algorytmu Stochastycznej Metody Elementów Skończonych dla losowo określonego obciążenia wiatrem. Modelowanie niezawodności obejmuje tutaj funkcję graniczną określoną dla wychylenia i obrotu badanych konstrukcji. W obliczeniach wykonanych programem MES ROBOT oraz system algebry komputerowej MAPLE analizowano wieżę o wysokości 40,5 m. Osiągnięte wyniki potwierdzają hipotezę, iż wartości wskaźników niezawodności są bardzo wrażliwe na losowy rozrzut parametrów obciążenia wiatrem.

The main aim of this elaboration is an application of the numerical analysis based on the generalized stochastic perturbation method and the response function technique for a determination of the reliability indices. The subject of this study is the stainless steel telecommunication tower spatial structure. Those indices are determined thanks to the Stochastic Finite Element Method for the randomized uncertain external loading of the wind. Reliability analysis obeys the limit function defined for the deflection and rotation of the discretized structures. The computational part is completed using the commercial FEM system ROBOT and computer algebra system MAPLE and is focused on the tower having 40,5 meters. The results confirm the general hypothesis that the values of the reliability indices are very sensitive to the random dispersion of the structural and external loadings parameters.
On computer modeling of reliability for the steel telecommunication towers